Tyrphostin AG556 increases the activity of large conductance Ca2+‐activated K+ channels by inhibiting epidermal growth factor receptor tyrosine kinase. Issue 9 (14th March 2017) - Wang, Yan; Sun, Hai‐Ying; Liu, Ying‐Guang; Song, Zheng; She, Gang; Xiao, Guo‐Sheng; Wang, Yan; Li, Gui‐Rong; Deng, Xiu‐Ling
Abstract: The present study was designed to investigate whether large conductance Ca 2+ ‐activated K + (BK) channels were regulated by epidermal growth factor (EGF) receptor (EGFR) tyrosine kinase. BK current and channel tyrosine phosphorylation level were measured in BK‐HEK 293 cells expressing both functional α‐subunits and the auxiliary β1‐subunits using electrophysiology, immunoprecipitation and Western blotting approaches, respectively, and the function of rat cerebral basilar arteries was determined with a wire myography system. We found that BK current in BK‐HEK 293 cells was increased by the broad spectrum protein tyrosine kinase (PTK) inhibitor genistein and the selective EGFR tyrosine kinase inhibitor AG556, one of the known tyrphostin. The effect of genistein or AG556 was antagonized by the protein tyrosine phosphatase (PTP) inhibitor orthovanadate. On the other hand, orthovanadate or EGF decreased BK current, and the effect was counteracted by AG556. The tyrosine phosphorylation level of BK channels (α‐ and β1‐subunits) was increased by EGF and orthovanadate, while decreased by genistein and AG556, and the reduced tyrosine phosphorylation of BK channels by genistein or AG556 was reversed by orthovanadate. Interestingly, AG556 induced a remarkable enhancement of BK current in rat cerebral artery smooth muscle cells and relaxation of pre‐contracted rat cerebral basilar arteries with denuded endothelium, and these effects were antagonized by the BK channel blocker paxilline or orthovanadate. These results demonstrate that tyrosine phosphorylation of BK channels by EGFR kinase decreases the channel activity, and inhibition of EGFR kinase by AG556 enhances the channel activity and dilates rat cerebral basilar arteries.